Qualidade de vida de pessoas vivendo com HIV atendidas em serviços públicos de saúde [Quality of life of people living with HIV treated in public health services] [Calidad de vida de personas viviendo con VIH atendidas en servicios públicos de salud] - Cecilio, Hellen Pollyanna Mantelo; Oliveira, Daniela Sousa; Marques, Sergio Correa; Apostolidis, Thémistoklis; Oliveira, Denize Cristina (Revista Enfermagem UERJ, 2019)
Quality of life of people living with HIV treated in public health services [Qualidade de vida de pessoas vivendo com HIV atendidas em serviços públicos de saúde] [Calidad de vida de personas viviendo con VIH atendidas en servicios públicos de salud] Objective: to describe the profile and evaluate the quality of life of people living with HIV treated in public health services. Methods: in this cross-sectional, quantitative study of 281 people living with HIV treated in public health services in the municipalities of Rio de Janeiro and Niteroi, data were collected using a socioeconomic and clinical instrument and the WHOQOL-HIV brief questionnaire, and analyzed by descriptive statistics, with research ethics committee approval. Results: the sample comprised mainly men, with income of up to two minimum wages and a positive perception of their health. Most facets of quality of life were positively assessed, with the highest averages in the psychological, social relations, spirituality, religion and personal beliefs domains, and the lowest, in the environmental domain. Conclusion: the profile of people living with HIV corroborates national data, and the assessment of quality of life was more positive than in other studies. RESUMO Objetivo: descrever o perfil e avaliar a qualidade de vida de pessoas vivendo com HIV atendidas em serviços públicos de saúde. Métodos: estudo transversal, quantitativo com 281 pessoas vivendo com HIV atendidas em serviços públicos de saúde nos municípios do Rio de Janeiro e Niterói. Os dados foram coletados por meio de instrumento de dados socioeconômicos e clínicos e do WHOQOL-HIV bref, analisados por estatística descritiva, após aprovação do Comitê de Ética em Pesquisa. Resultados: a amostra foi composta majoritariamente por homens, renda de até dois salários mínimos e percepção positiva da saúde. A qualidade de vida foi positivamente avaliada na maioria das facetas, as maiores médias foram nos domínios: psicológico, relações sociais, espiritualidade, religião e crenças pessoais e a menor no domínio meio ambiente. Conclusão: o perfil das pessoas vivendo com HIV corrobora, os dados nacionais e a avaliação da qualidade de vida foi mais positiva do que em outros estudos. RESUMEN Objetivo: describir el perfil y evaluar la calidad de vida de personas viviendo con VIH atendidas en servicios públicos de salud. Métodos: estudio transversal, cuantitativo, junto a 281 personas viviendo con VIH, atendidas en servicios públicos de salud en los municipios de Río de Janeiro y Niterói. Se han recolectado los datos mediante un instrumento de datos socioeconómicos y clínicos y del WHOQOL-HIV bref, analizados por estadística descriptiva, después de la aprobación del Comité de Ética en Investigación. Resultados: la muestra se compuso mayoritariamente de hombres, con ingresos de hasta dos salarios mínimos y percepción positiva de la salud. Se evaluó positivamente la calidad de vida en la mayoría de las facetas, los promedios más altos en los dominios: psicológico, relaciones sociales, espiritualidad, religión y creencias personales y el más bajo en el dominio medio ambiente. Conclusión: el perfil de las personas que viven con VIH corrobora con los datos nacionales y la evaluación de la calidad de vida fue más positiva que en otros estudios.